Analisis Belanja Modal, Pendapatan Asli Daerah, dan Dana Perimbangan Terhadap Pertumbuhan Ekonomi Provinsi Jambi Periode 2012 - 2021 - Neldawaty, Rika; -, Suherman (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2024)
This study aims to determine the Analysis of Capital Expenditure, Local Own Revenue and Balancing Funds on Economic Growth in Regencies/Cities in Jambi Province. The type of research used in this research is quantitative research. The data processed is secondary data from Capital Expenditures, Regional Original Income, Balancing Funds and Regency/City Economic Growth in Jambi Province in 2012 – 2021. The results showed that simultaneously Capital Expenditure, Regional Original Income and Balancing Funds have a significant effect on Economic Growth in Jambi Province, this is proven by a significance value that is smaller than the probability (0.000 < 0.05). Partially, capital expenditure has a significant effect on economic growth in Jambi Province, as evidenced by a significant value that is smaller than the significant probability (0.0112 < 0.05) and partially Own-Owned Income has no significant effect on economic growth in Jambi Province, as proven by the value significance is smaller than the probability of significance (0.2067 > 0.05) while the Balancing Fund has a significant effect on Economic Growth in Jambi Province, as proven by the significance value which is smaller than the probability of significance (0.0000 < 0.05)